Does Socially Responsible Supplier Selection Pay Off for Customer Firms? A Cross‐Cultural Comparison. Issue 3 (24th July 2013) - Thornton, LaDonna M.; Autry, Chad W.; Gligor, David M.; Brik, Anis Ben
<x xml:space="preserve">Abstract</x> Building on Carter and Jennings' (2002a, b, 2004) seminal works on socially responsible purchasing and logistics, this multinational study investigates the extent to which socially responsible supplier selection (SRSS) is associated with customer firms' financial performance in three key world economic regions. We collect and utilize a unique dataset consisting of a total of 479 manufacturing, retail, and service provider firms operating in three distinct national cultures: China, the United Arab Emirates, and the United States of America. Based on an exploratory empirical analysis, we observe evidence that, overall, firms that consider social responsibility aspects during the supplier selection process enjoy financial performance advantages versus rivals. However, model comparisons across the studied countries reveal differential outcomes of SRSS by region. Our findings aid supply chain managers by linking SRSS to commonly expected outcomes within these important national settings.